Tributaries of the hepatic vein in the ostrich (Struthio camelus) - Ferreira, Nalva Fatima [UNESP]; de Carvalho, Roberto Gameiro [UNESP]; de Souza, Wilson Machado [UNESP]; de Souza, Nair Trevizan Machado [UNESP]; de Melo, Alan Peres Ferraz [UNESP]; Rodrigues, Rosangela Felipe [UNESP] (FapUNIFESP (SciELO), 2020)
The ostrich (Struthio camelus, Linnaeus 1758) is the largest bird in the world. It is of great economic importance in Africa and is found across several countries. With developments in breeding systems, morphological studies that facilitate the application of the knowledge are necessary, considering the species has unique anatomical features. The objective of the present study was to describe the major tributaries of the hepatic vein in the species. Ten viscera of adult individuals of both sexes, which were injected with Neoprene latex through the hepatic vein, were used to visualize their tributaries. After the vascular repletion, the tissues were fixed and conserved in 10% formaldehyde aqueous solution. The hepatic carrier system was dissected and photo-documented. The left hepatic vein receives blood from the proventricle and gastric ventricle, while the right hepatic vein is responsible for the drainage of blood into the following organs: spleen, through the proventriculosplenic vein; pancreas, through the pancreaticoduodenal vein; jejunum, through the jejunum trunk; and the colon, which forms the cranial mesenteric vein.
Afluentes da veia porta-hepática no avestruz (Struthio camelus)
Keywords: Hematous vein; Struthio camelus; Venous drainage